Progression on spectrum sensing for cognitive radio networks: A survey, classification, challenges and future research issues. (1st October 2019) - Gupta, Mani Shekhar; Kumar, Krishan
Abstract: It is widely believed that the advances of networking technologies will reshape the future of telecommunication system. The continuous growth in data traffic originated by mobile users will be witnessed very serious problem in future. By 2021, the number of mobile users connected to the networks is expected to exceed 28.3 billion. The present policy of fixed spectrum allocation governed by authorized bodies is incapable to accommodate this increased traffic. This explosive growth of global mobile data traffic enjoins resolutely global research attention on cognitive radio networks. In this direction, this paper provides the current state of the art in survey-style and a taxonomy of the relevant work with detailed classification and mathematical modeling of various spectrum sensing schemes for complete cognitive cycle in an informational fashion. The contribution of this paper is threefold. In the first stage, an extensive review of the basic cognitive radio technology with complete cognitive cycle and features are presented. In second stage, various aspects of different spectrum sensing schemes are modeled. Furthermore, In third stage, this work outlines the applications, open issues and research directions for cognitive radio networks which contribute an overview of the active research initiatives in the area of spectrum sensing and encourage the future studies and research activities.